Spodoptera litura F. Immune System Against Exposure to the Biopesticide Mirabilis jalapa L. - Maulina, Dina; Sumitro, Sutiman Bambang; Lestari, Sri Rahayu; Djoa, Dominikus Djago (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
Synthetic insect repellent contributed to increasing farm products. This research studies the influence of an extract of Mirabilis jalapa. It is a vegetative insect repellent. It was applied to the polyphagous pest's cellular and humoral immune reactions, Spodoptera litura. This study targeted the body's resistant reaction to S. litura at the cellular and humoral tiers after contacting biopesticides from M. jalapa extracts. This research examined the process of cellular counteraction by assessing the varieties of hemocytes employing the ANOVA test and a phagocytosis test using percentages. The function of the humoral-resistant counteraction was assessed by phenoloxidase analysis employing the ANOVA test. The results demonstrated that a 0.2% M. jalapa concentrate solution noticeably affected the numbers of prohemocytes, granular cells, oenocytoid cells, and spherules compared to reference samples (p<0.05). Moreover, sub-lethal levels show noticeable kinds in PO enzyme levels (p<0.05), with a notable improvement after one hour of handling. Phagocytosis, on the other hand, demonstrated a drop in the ratio of phagocytic cells at 0.4% dose concentrations contrasted to the control group, suggesting a hidden impact on the pest's resistant response. This research reveals that the ability of M. jalapa extract as a biopesticide with immunosuppressive effects on S. litura.